2009
DOI: 10.3892/or_00000332
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of altered expression of SDC2 and CYR61 in esophageal squamous cell carcinoma

Abstract: Abstract. The transforming growth factor ß (TGF-ß) signaling pathway plays an important role in growth and development, and is critically involved in the genesis and development of tumors. Syndecan-2 (SDC2) and Cysteine-rich 61 (CYR61) are important genes in this pathway and SDC2 is known to be a significant upstream regulator of TGF-ß signaling. However, the roles of SDC2 and CYR61 in the development of esophageal squamous cell carcinoma (ESCC) remain unclear. In the present study, we investigated the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…In addition, its role in angiogenesis is supported by various data such as its high expression in the microvasculature of mouse glioma tumors (31), or its essential role in the sprouting of new blood vessels during zebrafish embryogenesis (34) and in many steps of human “ in vitro ” neovascularization (35). Interestingly, however, in the tumors analyzed in this work there was a good positive correlation between SDC2 levels and patient survival, data that has also been described in esophageal squamous cell carcinoma, prostate cancer, and pancreatic ductal adenocarcinoma, leading to the proposal that the expression levels of this molecule are of interest for diagnosis (36–38). These observations can be related to data suggesting a role for this PG as a metastasis inhibitor; thus a highly metastatic variant of Lewis lung carcinoma cells displays low SDC2 expression, and this molecule is able to suppress activation of matrix metalloproteinase-2 (39); Furthermore, it has been described that osteosarcoma cells that overexpress SDC2 are restricted in their migration and also exhibit enhanced apoptosis in vitro (40).…”
Section: Discussionsupporting
confidence: 57%
“…In addition, its role in angiogenesis is supported by various data such as its high expression in the microvasculature of mouse glioma tumors (31), or its essential role in the sprouting of new blood vessels during zebrafish embryogenesis (34) and in many steps of human “ in vitro ” neovascularization (35). Interestingly, however, in the tumors analyzed in this work there was a good positive correlation between SDC2 levels and patient survival, data that has also been described in esophageal squamous cell carcinoma, prostate cancer, and pancreatic ductal adenocarcinoma, leading to the proposal that the expression levels of this molecule are of interest for diagnosis (36–38). These observations can be related to data suggesting a role for this PG as a metastasis inhibitor; thus a highly metastatic variant of Lewis lung carcinoma cells displays low SDC2 expression, and this molecule is able to suppress activation of matrix metalloproteinase-2 (39); Furthermore, it has been described that osteosarcoma cells that overexpress SDC2 are restricted in their migration and also exhibit enhanced apoptosis in vitro (40).…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, miR-9 was involved in suppression of inflammatory responses in atherosclerosis, wherein miR-9 inhibited the activation of the NLRP3 inflammasome, and thus attenuated atherosclerosisrelated inflammation through the JAK1/STAT signaling pathway (Wang et al, 2017). Moreover, the SDC2 gene plays a key role in the regulation of the TGF-β signaling pathway as a co-receptor for growth factors (Huang et al, 2009). Another study also documented the elevation of SDC2 during atherosclerotic plaque formation (Geeraert et al, 2007), suggesting that inhibition of SDC2 could suppress the process of atherosclerotic plaque formation, which is very much in line with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Web-available microarray analysis further indicated that Syndecan-2 (SDC2) is a potential target gene of miR-9. SDC2 is known to serve as a cell surface receptor which mediates adhesion-dependent signal transduction in the process of cell growth, migration, and differentiation (Huang et al, 2009). SDC2 has also been documented to exert particular effects on atherosclerotic plaque formation (Geeraert et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…37,61 Huang et al observed that the downregulation of SDC2 was associated with poor prognosis in esophageal squamous cell carcinoma. 62 Another study showed that SDC2 was hypermethylated in tumor tissue samples of gastric cancer patients compared with the corresponding non-tumor mucosa (CNM). 63 As the first step in our study, the SDC2 promoter was found to be strongly hypermethylated by pyrosequencing both in colonic adenoma and CRC samples compared with unmethylated healthy controls.…”
Section: Discussionmentioning
confidence: 99%